Complement analysis in children with idiopathic membranoproliferative glomerulonephritis: a long-term follow-up - Schwertz, Rainer; Rother, Ursula; Anders, Dietrich; Gretz, Norbert; Schärer, Karl; Kirschfink, Michael (Pediatric allergy and immunology, 2001)
Fifty children with idiopathic membranoproliferative glomerulonephritis (MPGN), aged 2-14 years at apparent onset, were monitored for the presence of C3 nephritic factor (C3 NeF) and signs of complement activation in serum. In addition, C3 allotyping was performed in 32 patients. Observation time ranged from 2 to 20 (median 11) years. C3 NeF activity was detected at least once in 60% of the patients (in 11 of 26 with type I, in 15 of 17 with type II, and in four of seven with type III). C3 NeF-positive patients had significantly reduced levels of CH50 and C3 and elevated levels of C3dg/C3d. During follow-up, C3 levels were persistently normal in 62% of the patients with MPGN type I and in 43% with type III but in only 18% with type II. C3 allotype frequencies differed from those found in healthy controls with a significant shift to the C3F/C3FS variants in C3 NeF-positive patients. C3b(Bb)P as a marker for alternative pathway activation was not increased in C3 NeF-positive patients. Despite the presence of C3 NeF activity, C3 levels remained normal in six patients throughout the observation period. C3 NeF became undetectable in six patients, whereas seven developed C3 NeF activity during follow-up. There was no significant difference in renal survival probability in patients with or without C3 NeF activity. Neither C3 variants nor continous low C3 or low CH50 levels had any prognostic value for the clinical outcome. No factor H deficiency was detected.
Gesehen am 17.02.2021
First published: 21 December 2001